Investigating pyrolysis kinetics of lignocellulosic agro-waste (coconut shell) and plastics (PP & HDPE) through distributed activation energy model - Harsh V. Rambhia; Vikram S. Chatake; Aniruddha B. Pandit (Next Energy)
This study addresses the critical need to manage plastic waste and explore alternative energy sources due to their intertwined impacts on environmental degradation and climate change. By investigating the pyrolysis of lignocellulosic biomass (coconut shells) and thermoplastic polymers (polypropylene [PP] and high-density polyethylene [HDPE]) using Thermo-Gravimetric Analysis (TGA) and Distributed Activation Energy Model (DAEM). The research aims to optimize the pyrolysis condition for producing valuable fuels and chemicals. The study evaluates activation energy, possible reaction mechanisms, and process efficiency, offering insights into sustainable energy production from waste materials. The apparent average activation energy obtained for coconut shell pyrolysis ranges between 187.84 and 199.31 kJ/mol, while for plastic it ranges between 169.15 and 360.04 kJ/mol.